Innovation and productivity in services: Evidence from Germany, Ireland and the United Kingdom - Bettina Peters; Rebecca Riley; Iulia Siedschlag; Priit Vahter; John McQuinn (The Economic and Social Research Institute (ESRI), 2014)
We examine the links between innovation investment, innovation output and productivity in service enterprises. For this purpose, we use micro data from the Community Innovation Surveys 2006-2008 in Germany, Ireland, and the United Kingdom and estimate an augmented structural model which links innovation inputs, innovation outputs and productivity. Our estimates suggest that innovation in service enterprises was linked to higher productivity. In all three countries analysed, amongst the innovation types that we consider, the strongest link between innovation and productivity was found for marketing innovations. Successful innovation in service enterprises appears to be associated with enterprise size, innovation expenditure intensity (in Germany and the United Kingdom), foreign ownership (Ireland), exporting and engagement in co-operation for innovation activities. The determinants of innovation in service enterprises appear remarkably similar to the determinants of innovation in manufacturing enterprises.
Keywords: F61; L25; O31; 330; internationalisation of services; innovation; productivity